The Creation of Myth: Starting the First "Great Debate" in International Relations Theory - T. A. Alekseeva (Vestnik MGIMO-Universiteta, 2015)
From one textbook to another wanders the story about three (sometimes - four) Great debates, which formed the canonical history of the theory of international relations. In reality everything was much more complicated, and the theoretical richness much wider than many times repeated antinomic pairs - realism vs. idealism, traditionalism vs. modernism, rationalism vs. reflectivism The author regards the discussions between different trends of the political thought in the interwar period, which were later called the First "Great Debates", which, according to the author's view were pre-paradigmal.